2020
DOI: 10.1038/s41598-020-67244-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of T2-FLAIR mismatch sign in lower-grade gliomas

Abstract: T2-FLAIR mismatch sign is known as a highly specific imaging marker of IDH-mutant astrocytomas. This study was intended to clarify what the T2-FLAIR mismatch sign represents by pathological analysis of lower-grade gliomas rediagnosed in accordance with the WHO 2016 classification. We retrospectively analyzed the records of 64 patients diagnosed with WHO grade II and III diffuse gliomas between June 2009 and November 2018. T2-FLAIR mismatch sign was found in 10 (45%) out of 22 patients with IDH-mutant astrocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 18 publications
(36 reference statements)
3
34
0
Order By: Relevance
“…Since T2-FLAIR mismatch occurs based on the long T1-relaxation time, the intratumoral cystic component simulates a T2-FLAIR mismatch. The T2-FLAIR mismatch false positive results have been reported in previous studies [15,17]. Therefore, surgical specimens are still needed to diagnose gliomas instead of relying on the T2-FLAIR mismatch sign alone.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Since T2-FLAIR mismatch occurs based on the long T1-relaxation time, the intratumoral cystic component simulates a T2-FLAIR mismatch. The T2-FLAIR mismatch false positive results have been reported in previous studies [15,17]. Therefore, surgical specimens are still needed to diagnose gliomas instead of relying on the T2-FLAIR mismatch sign alone.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported that the T2-FLAIR mismatch sign has been shown to predict astrocytoma, IDH-mutant with 95-100% speci city [14,15]; however, sensitivity has been low at 46-51% [8, 14, 16]. Inter-rater agreement has been shown to have a wide range of κ = 0.38-0.88 [5,8,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The pooled sensitivity and specificity rates were estimated to be as high as 31% and 100%, respectively. Moreover, Deguici et al reported that the T2–FLAIR mismatch sign was found in 45% of the 22 patients with IDH mutant astrocytoma and in only 5% of those with oligodendroglioma or IDH wild-type astrocytoma [ 18 ]. In the latter study, the positive predictive value of the T2–FLAIR mismatch sign was as high as 83% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Deguici et al reported that the T2–FLAIR mismatch sign was found in 45% of the 22 patients with IDH mutant astrocytoma and in only 5% of those with oligodendroglioma or IDH wild-type astrocytoma [ 18 ]. In the latter study, the positive predictive value of the T2–FLAIR mismatch sign was as high as 83% [ 18 ]. Throckmorton et al claimed that broadening the criteria to include T2-heterogeneous LGG lesions increased the sensitivity of the T2–FLAIR mismatch sign by 30% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation